Palladium-Catalyzed Cyanation of Nonactivated Alkynes; Development of Cyanopalladation and Its Application to Cyclization and Cycloaddition Reactions - Arai, Shigeru; Nishida, Atsushi (Synlett, 2012)
This account describes the cyanopalladation of simple and nonactivated alkynes and their application to various cyclization and cycloaddition protocols. A unique feature of cyanopalladation is the direct nucleophilic cyanation with an external CN source such as TMSCN of simple alkynes, which can be effectively activated by Pd(II) under molecular oxygen. There are two possible pathways: syn- and anti-cyanopalladation, which are strongly influenced by the structure of the substrates. The former is usually the major pathway because nucleophilic cyanation is favored to occur at the less hindered alkynyl carbon. The latter could be controlled by the Markovnikov rule, with cyanide directly attacking the π-complex of alkynyl carbons from the site opposite Pd(II). Once the cyanoalkenyl Pd(II) species are formed by cyanopalladation, these intermediates act as useful precursors for sequential carbon–carbon bond-forming reactions, such as 5-exo and 6-endo cyclizations and [4+2] cycloaddition. Cyclization is triggered by regio- and stereoselective cyanopalladation, and [4+2] cycloaddition gives up to five stereogenic centers through the formation of four C–C bonds in a single operation. The reaction pathways and the origin of stereochemistry are also described.1 Introduction2 Catalytic 1,2-Dicyanation 2.1 Terminal Alkynes2.2 Internal Alkynes2.3 Synthetic Applications3 Dicyanative Cyclization3.1 5-exo Cyclization3.2 Diyne Cyclization3.2.1 Terminal Diynes 3.2.2 Internal Diynes 3.3 6-endo Cyclization4 Dicyanative [4+2] Cycloaddition5 Conclusion
Keywords: alkynes; cyanation; cyanopalladation; enynes; [4+2] cycloaddition; cyclization